A wavelet analysis of Italian fiscal sustainability - Cosimo Magazzino; Mihai Mutascu (Journal of Economic Structures, 2019)
In this paper, we analyse the relationship between public primary deficit and debt for Italian sustainability over the 1862-2013 years. Our empirical strategy uses the wavelet analysis. The empirical evidence suggests the presence of a substantial fiscal sustainability in the long run for Italy. This reversed much of the results of previous empirical literature, due to traditional time series approach and a shorter time horizon.
Keywords: C22; E62; H62; H63; 330; Fiscal sustainability; Wavelet analysis; Italy